Fabrication and characterization of cell sheets using methylcellulose and PNIPAAm thermoresponsive polymers: A comparison Study. Issue 5 (24th February 2017) - Forghani, Anoosha; Kriegh, Lisa; Hogan, Katie; Chen, Cong; Brewer, Gabrielle; Tighe, Timothy B.; Devireddy, Ram; Hayes, Daniel
Abstract: Culturing cells on thermoresponsive polymers enables cells to be harvested as an intact cell sheet without disrupting the extracellular matrix or compromising cell‐cell junctions. Previously, cell sheet fabrication methods using methylcellulose (MC) gel and PNIPAAm were independently demonstrated. In this study, MC and PNIPAAm fabrication methods are detailed and the resulting cell sheets characterized in parallel studies for direct comparison of human adipose derived stromal/stem cell (hASCs) sheet formation, cell morphology, viability, proliferation, and osteogenic potential over 21 days. A cell viability study revealed that hASCs in MC and PNIPAAm cell sheets remained viable for 21 days and proliferated until confluency. Osteogenic cell sheets exhibited upregulation of alkaline phosphatase (ALP) at day 7, as well as calcium deposition at 21 days. Additionally, expression of osteocalcin ( OCN ), a late‐stage marker of osteogenesis, was quantified at days 14 and 21 using RT‐PCR. OCN was upregulated in MC cell sheets at day 14 and PNIPAAm cell sheets at days 14 and 21. These results indicate that hASCs formed into cell sheets commit to an osteogenic lineage when cultured in osteogenic conditions. Cell sheets composed of hASCs may be used for further studies of hASC differentiation or surgical delivery of undifferentiated cells to defect sites. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1346–1354, 2017.